Studies on new isolates of native entomopathogenic fungi from the Argentinean Pampas region affecting grasshopper pest - Mancini, Micaela Anahí (2024)
Fungi are the most important entomopathogens in the natural regulation of insect populations. They have a wide distribution and significant advantages as biological control agents. Prospecting for new native strains of entomopathogenic fungi in the Pampas region has not yet been carried out. The main objectives of this study were isolating and identifying strains of different species of entomopathogenic fungi that naturally infect grasshopper species in the Pampas region and determining, through laboratory tests, their virulence and pathogenicity on nymphs of the pest grasshopper Dichroplus maculipennis. Furthermore, whether the phylogenetic relationships between Beauveria bassiana. isolates would be associated with virulence and pathogenicity or geographical distribution. Thirty-four isolates of entomopathogenic fungi were obtained from different grasshopper species corresponding to eleven sites in three counties in the center of Buenos Aires province. There were 31 isolates of B. bassiana and 3 of Metarhizium genus. These isolates scored 66.6% (LPSc 1443) and 100% (LPSc 144, LPSc 1445, and LPSc 1476) of mortality against third-instar nymphs of D. maculipennis, and these last cause death at 4.86 ± 0.20, 4.80 ± 0.17 and 5 ± 0.15 MST 50 days, respectively. An association between phylogenetic relationships and geographical distances in B. bassiana was found.